2015
DOI: 10.7759/cureus.396
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactivity of Rapid Salmonella Typhi IgM Immunoassay in Dengue Fever Without Co-Existing Infection

Abstract: Introduction: Dengue fever is endemic in developing nations worldwide with as many as 500,000 annual cases of dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). A prompt and accurate diagnosis early in the disease course is essential for prompt identification and treatment of severe complications of the dengue virus infection (DVI). We identified cross-reactivity of a rapid IgM test for typhoid fever in patients with febrile illnesses that were determined to be due to dengue virus.Methods: All pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
(17 reference statements)
2
6
1
Order By: Relevance
“…Many studies had reported that Salmonella typhi somatic and flagella antigen is shared by large number of organism from Enterobacteriaceae family 9,10 and even in several other febrile illness such as Malaria, Tuberculosis, Schistosomiasis and in Dengue virus infection there are reports of false sero positivity of Widal test where there is no signs and symptoms of acute Salmonella infection. 7,[11][12][13] In a recent study by Seema et al 14 had reported around 20% of their COVID-19 positive patients were shown false positive result of Widal test which is similar to our study finding where we reported 20% of our COVID-19 patients had a significant titre of Widal test. Yet in another study from India by Adata et al also find similar finding in their study population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Many studies had reported that Salmonella typhi somatic and flagella antigen is shared by large number of organism from Enterobacteriaceae family 9,10 and even in several other febrile illness such as Malaria, Tuberculosis, Schistosomiasis and in Dengue virus infection there are reports of false sero positivity of Widal test where there is no signs and symptoms of acute Salmonella infection. 7,[11][12][13] In a recent study by Seema et al 14 had reported around 20% of their COVID-19 positive patients were shown false positive result of Widal test which is similar to our study finding where we reported 20% of our COVID-19 patients had a significant titre of Widal test. Yet in another study from India by Adata et al also find similar finding in their study population.…”
Section: Discussionsupporting
confidence: 89%
“…Several other investigator also find the similar findings where they reported about 50% of their study population have dengue IgM with significant Widal test titre. 7 We also observed that in case of SARS-COV-2 infected patients around 20% subjects showed titre of anti O≥80 and titre of anti H were ≥160 which is considered as a base line titre of the local population. However, around 18% of the patients had anti O titre of 1: 20 and anti H of 1:40.…”
Section: Discussionmentioning
confidence: 54%
“…The antibody decay profiles showed IgG antibodies persisted over 12 months after infection while the IgM and IgA antibodies appeared to decline after 3 to 4 months post infection. Another important limitation of antibody testing is that false positives may occur due to cross-reactivity resulting from other infections [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This disagreement between blood culture and widal result might be due to the fact that Widal test is based on the reaction of S. Typhi antigens (O and H) to speci c antibodies in patient's serum where cross reactivity with similar antigens is possible. Cross reactivity of widal has been reported in patients with dengue fever by Bhatti et al (2015) where they recruited patients who had clinical and serological evidence of dengue virus infection and subjected them to widal screening test. They found about 33% of the patients with dengue fever to be widal positive with no single Salmonella Typhi bacterium isolated from their blood.…”
Section: Discussionmentioning
confidence: 99%